Teknik Persuasi dalam Komunikasi Agama: Studi Kasus Program “Kurban sampai Pelosok” UNS Surakarta - Sihabuddin; Riyanto, Buddy (Jurnal Komunikasi Islam, 2025)
This study examines the persuasive communication strategies employed by the organizers of the "Kurban sampai Pelosok (Qurban to the Remote Areas) "program, initiated by the Zakat Collection Unit (UPZ) at Sebelas Maret University (UNS) Surakarta. The research was motivated by the consistent yearly increase in the number of sohibul qurban (qurban donors), which has continuously surpassed the program’s target. Employing a qualitative case study approach, data were collected through in-depth interviews with program coordinators and direct observations at the UPZ UNS office. The findings reveal that the program’s success is closely tied to the effectiveness of persuasive communication strategies. These include: (1) rebranding the tagline from “Kurban dari Kampus (Qurban from Campus)” to “Kurban sampai Pelosok (Qurban to the Remote Areas)”; (2) crafting diverse and creative message content; and (3) disseminating information consistently across various social media platforms and official UPZ UNS channels.